Improving Students Activity and Students Learning Outcomes by Using Creative Problem Solving Learning with Used Box Props - Roziqin Khoirur; Abd Rahman (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2017)
The purpose of the research to describe the using of creative  problem solving with used box props and to describe the using of creative  problem solving with used box props cam improve the students learning outcomes. The kind of the research is PTK with qualitative and quantitative approach. The subjects of the research are students of class VIII B at MTs. Zahrotul Islam. With the data collecting method that used in the research are documentation, observation, interview and test. The data analysis method that used is qualitative and quantitative. The results of the research there is increased activity and student learning outcomes.Keywords: creative  problem solving, used box props,and learning outcomes